An evolutionary dynamic of trade union systems - Wolfgang Streeck; Jelle Visser (Max-Planck-Institut für Gesellschaftsforschung, 1998)
In recent years, parallel trends of organizational restructuring have become manifest among trade unions. Sharing similar experiences of stagnant membership and falling density rates, coupled with structural shifts in employment from industry to services and a growing pressure to attend to the needs of more heterogeneous constituencies under increasingly decentralized labor-management relations, trade unions must adapt their internal operation and external representation. In particular, unions seem to suffer from the same inverse fluctuation of revenue and client needs as social security systems, as the economics of union organizing require that most members, most of the time, do not call upon the union's services except for the collective protection it offers. In many countries, trade unions are now in a process of regrouping in which sectoral boundaries are becoming increasingly unimportant. Drawing on the case histories of union development in Germany and the Netherlands, the paper shows that current changes in the organizational landscape of trade unions are not based on political strategies of interest representation, grounded in visions of class unity or industrial governance, but are driven by an evolutionary dynamic of unions as service organizations which must respond to general principles of adaptive-economic rationality. – – In den letzten Jahren lassen sich bei Gewerkschaften verschiedener Länder parallele Prozesse organisatorischer Umstrukturierung beobachten. Angesichts stagnierender Mitgliederzahlen und sinkender Organisationsgrade, Verschiebungen der Beschäftigung vom industriellen zum Dienstleistungssektor sowie der Notwendigkeit, den Bedürfnissen einer heterogener werdenden Mitgliedschaft bei zunehmend dezentralisierten Arbeitsbeziehungen gerecht zu werden, sehen sich die Gewerkschaften gezwungen, ihre Organisation nach innen ebenso zu überdenken wie ihre Politik nach außen. Insbesondere scheinen Gewerkschaften mit derselben gegenläufigen Entwicklung von Einnahmen und Mitgliederansprüchen konfrontiert zu sein wie die Sozialversicherungsträger, wobei die Ökonomie gewerkschaftlicher Organisierung voraussetzt, daß die meisten Mitglieder die von der Gewerkschaft angebotenen Dienstleistungen in der Regel nicht in Anspruch nehmen. In zahlreichen Ländern durchlaufen die Gewerkschaften heute eine Phase raschen organisatorischen Wandels, bei dem Abgrenzungen zwischen Wirtschafts-zweigen zunehmend unbedeutend werden. Das Papier zeigt am Beispiel von Deutschland und den Niederlanden, daß die gegenwärtigen Veränderungen der organisatorischen Gewerkschaftslandschaft nicht in erster Linie von politischen Strategien der Interessenvertretung oder gar von Visionen solidarischer Klasseneinheit oder industrieller Selbstregierung getrieben werden, sondern von einer evolutionären Dynamik von Gewerkschaften als Dienstleistungsorganisationen, die allgemeinen Prinzipien adaptiv-ökonomischer Rationalität gehorchen müssen.
Keywords: 300